2020
DOI: 10.3389/fneur.2020.603161
|View full text |Cite
|
Sign up to set email alerts
|

Association of MRI Measures With Disease Severity and Progression in Progressive Supranuclear Palsy

Abstract: Objective: To verify the association of midbrain-based MRI measures as well as cortical volumes with disease core features and progression in patients with Progressive Supranuclear Palsy (PSP). Methods: Sixty-seven patients (52.2% with Richardson's syndrome) were included in the present analysis. Available midbrain-based MRI morphometric assessments as well as cortical lobar volumes were computed. Ocular, gait and postural involvement at the time of MRI was evaluated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Survival in PSP‐Richardson syndrome can be predicted to some extent by the PSPRS total score and its progression rate early in the disease course 7,13 . Table 5 summarizes previous studies of factors associated with shorter survival in PSP 1,5,6,7,13,21,25‐31 . The present study does the same using a different methodology and further confirms the predicting value of the progression rate of downgaze palsy in survival.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Survival in PSP‐Richardson syndrome can be predicted to some extent by the PSPRS total score and its progression rate early in the disease course 7,13 . Table 5 summarizes previous studies of factors associated with shorter survival in PSP 1,5,6,7,13,21,25‐31 . The present study does the same using a different methodology and further confirms the predicting value of the progression rate of downgaze palsy in survival.…”
Section: Discussionsupporting
confidence: 75%
“…Early urinary symptoms Cui et al, 2020 29 Greater midbrain atrophy and enlarged third ventricle on MRI Picillo et al, 2020 30 Golbe et al, 2020 13 Velocity of total PSPRS score from onset to first visit progression in PSPRS scores during that limited timespan. 8 To extend this analysis to a longer time period, we used our longer term data set to tabulate the median and 95% CI total PSPRS scores and downgaze palsy scores through the seventh year of disease.…”
Section: Early Constipationmentioning
confidence: 99%
“…The LRRK2 gene was associated with reduced survival ( 20 ). Atrophy in midbrain and larger third ventricle width were also associated with higher risk of death ( 21 , 22 ). We were unable to control all the factors in our study revealing that the rapid deterioration of the downgaze palsy could predict survival in an individual level, although we controlled other factors and also consistently found that older age of onset was also associated with a shorter disease duration to death.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the SCP, MCP, pons area and midbrain area allow the calculation of the MRI parkinsonism index (MRPI), wherein a value of ≥13.55 or The MRPI and the P area/M area ratio have adequate diagnostic value to support the PSP-RS clinical diagnosis of PSP-RS, as opposed to PD and healthy controls, but they do not show an adequate sensitivity and specificity profile when differentiating PSP subtypes [54]. Midbrain area measurement is much easier for neuroradiologists to perform, has similar diagnostic potential to MRPI, and is significantly associated with greater ocular motor dysfunction at the time of MRI and more rapid disease progression at follow-up [62]. Callosal atrophy and mild cortical atrophy -usually restricted to the frontal lobes -are also observed [47].…”
Section: Clinical Vignettementioning
confidence: 99%